Lignin Degradation in Pulp Mill Effluents by White Rot Fungi and the Role of Urea Addition - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1999)
ABSTRACT: Martani, E., A. Marwata, and I.D. Prijambada. 1999. Lignin degradation in pulp mill effluents by white rot fungi and the role of urea addition. Bi%gi, 2(7): 317-328. The ratio of C-N is important in lignin biodegradation by white rot fungi. This research was conducted to study degradation of lignin in pulp mill effluents by white rot fungi and the role of urea addition in the biodegradation. Culture selection was based on lignolytic activity and tolerancy to Chlor compound. Urea was added into the effluent to reach C-N ratio 10 or 20. Fermentation was conducted on a rotary shaker. The results showed that the effluent is potencial for causing enviommental pollution. Coriolus versicolor has highest lignolytic and tolerancy to Chlor compound compared with Phanerochaete sordida and P. chrysosporium. Inoculation of C. versicolor into 100% of pulp mill effluent and 10% of black liquor enhanced lignin degradation. Decolorization of pulp mill effluent, as a criterium of lignin degradation, was obtained either in inoculated and uninoculated treatments. However, C. versicolor inoculation showed a tendency enhancement of decolorization. Urea addition into black liquor increased the rate of lignin degradation and the growth of C. versicolor. Lignin degradation in black liquor with C-N ratio 10 was higher than those in higher ratios.